An improved system for the targeted mutagenesis of the psbA2 gene in Synechocystis sp. PCC 6803: mutation of D1-Glu244 to His impairs electron transfer between QA and QB of Photosystem II. Issue 2 (3rd April 2019) - Forsman, Jack A.; Winter, Regan T.; Eaton-Rye, Julian J.
ABSTRACT: The cyanobacterium Synechocystis sp. PCC 6803 has three copies of the psbA gene encoding the D1 reaction centre protein of Photosystem II (PS II). We have designed a mutagenesis system that allows introduction of mutations into the constitutively expressed psbA2 copy without affecting the expression of any flanking genes. A triple deletion strain was constructed in which psbA1 and psbA3 were removed by markerless deletions and psbA2 was replaced by a chloramphenicol-resistance cassette. A vector was then designed to enable the reintroduction of psbA2 in the chromosome using a kanamycin-resistance cassette as a selectable marker. This system was used to generate a control strain, which had an unmodified copy of psbA2, and two mutant strains which contained a copy of psbA2 where the codon for D1-Glu244 had been mutated to code for a His or Asp. The D1-Glu244 residue was targeted as it has been hypothesised to participate in a hydrogen-bond network that is required for protonation of the PS II secondary plastoquinone electron acceptor QB . While the phenotype of the control strain was similar to wild type, the E244H mutant exhibited impaired oxygen evolution and altered electron transfer between the primary quinone acceptor QA and QB . However, substitution of Glu-244 by Asp resulted in a mutant more closely resembling the control strain.